A Retrospective Evaluation of Mandibular Fracture in Kabul, Afghanistan - Ahmadi SU; Fayaz Y; Miri SAS; Wikins WM; Nazari FA; Karimi AN; Yaqubi I; Nikzad NA; Joya M; Fahimi R (Clinical, Cosmetic and Investigational Dentistry)
Shahab Uddin Ahmadi,1 Yahya Fayaz,1 Said Ahmad Sorosh Miri,2,3 Wakil Muhammad Wikins,4 Fareed Ahmad Nazari,5 Ali Naqi Karimi,4 Ismail Yaqubi,4 Naseer Ahmad Nikzad,4 Musa Joya,6 Reza Fahimi7 1Department of Stomatology, Khatam AL Nabieen University, Kabul, Afghanistan; 2Department of Prosthodontics, Khatam AL Nabieen University, Kabul, Afghanistan; 3Department of Stomatology, Kabul University of Medical Science “abu Ali Ibn Sina”, Kabul, Afghanistan; 4Department of Oral & Maxillofacial Surgery, National Curative and Specialized Stomatology Hospital, Kabul, Afghanistan; 5Department of Emergency Surgery & Trauma, Kabul University of Medical Science, Kabul, Afghanistan; 6Department of Physics, University of Surrey, Guildford, UK; 7Department of Clinic, Kateb University, Kabul, AfghanistanCorrespondence: Yahya Fayaz, Department of Stomatology, Khatam AL Nabieen University, Kabul, Afghanistan, Tel +93706281798, Email Dr.yahyafayaz@gmail.comBackground: The mandible, a key bone in the lower face, is prone to trauma. Although mandibular fractures are widely recognized as common and costly, there is a research gap on this topic in Afghanistan. This study explores the causes of lower jaw fractures and their link to demographic factors in the Afghan population.Materials and Methods: A retrospective analysis of 535 medical records from a Kabul tertiary hospital (March 2021 to March 2022) examined lower jaw fractures, patient demographics (age, sex), and injury causes. Statistical methods, including chi-square tests and Pearson’s contingency coefficient, were employed to explore correlations between mandibular fractures and demographic factors.Results: In this study, we analyzed 579 mandibular fractures in 535 patients, with road accidents (33.08%), falls (22.61%), and interpersonal conflicts being the leading causes. Most patients were aged 21– 30, with single fractures being the most common (92.3%) and parasymphyseal fractures being the most prevalent (28.5%). Although certain fracture types were significantly correlated with age, no notable association was found between age and injury cause.Conclusion: This study reveals that road accidents, falls, and interpersonal conflicts are the main causes of lower jaw fractures in Kabul, with the highest incidence in individuals aged 21– 30. These findings highlight the necessity for targeted public health interventions, such as improved road safety campaigns and stricter traffic regulation enforcement, to lower injury rates. Incorporating these insights into clinical practice can also help healthcare providers more effectively manage lower jaw fractures in affected populations.Keywords: lower jaw fracture, fracture patterns, trauma, accidents, Afghanistan